Kansas Editor Lauds Role of Press: Communicating Agricultural Research Results to the Public - Gary L. Vacin (Journal of Applied Communications, 1977)
When your director asked me to participate in your annual Experiment Station Conference this year, and told me the theme would be "Communicating Research Results," I was delighted.